Tear Lipocalin and Lipocalin-Interacting Membrane Receptor - Glasgow, Ben J. (Frontiers in Physiology, 2021)
Tear lipocalin is primate protein that was recognized as a lipocalin from homology of the primary sequence. The protein is most concentrated in tears and produced by lacrimal glands. Tear lipocalin is also produced in the tongue, pituitary, prostate, and the tracheobronchial tree. Tear lipocalin has been assigned a multitude of functions. The functions of tear lipocalin are inexorably linked to structural characteristics that are often shared by the lipocalin family. These characteristics result in the binding and or transport of a wide range of small hydrophobic molecules. The cavity of tear lipocalin is formed by eight strands (A-H) that are arranged in a β-barrel and are joined by loops between the β-strands. Recently, studies of the solution structure of tear lipocalin have unveiled new structural features such as cation-π interactions, which are extant throughout the lipocalin family. Lipocalin has many unique features that affect ligand specificity. These include a capacious and flexible cavity with mobile and short overhanging loops. Specific features that confer promiscuity for ligand binding in tear lipocalin will be analyzed. The functions of tear lipocalin include: anti-microbial activities, scavenger of toxic and tear disruptive compounds, endonuclease activity, and inhibition of cysteine proteases. In addition tear lipocalin binds and may modulate lipids in the tears. Such actions support a role as an acceptor for phospholipid transfer protein, heteropolymer formation to alter viscosity, and tear surface interactions. Its role as a promiscuous lipid binding protein has created opportunities as a drug carrier. Mutant analogs have been created to bind other molecules such as vascular endothelial growth factor for medicinal use. Tear lipocalin has been touted as a useful biomarker for several diseases including breast cancer, chronic obstructive pulmonary disease, diabetic retinopathy and keratoconus. The functional possibilities for tear lipocalin dramatically expanded when a putative receptor, lipocalin interacting membrane receptor was identified. However, opposing studies claim that lipocalin interacting membrane receptor is not specific for lipocalin. A recent study even suggests a different function for the membrane protein. This controversy will be reviewed in light of gene expression data that have not been previously considered.